Islamization of Knowledge: A Critique (American Journal of Islam and Society, 1994)
The Islamization of knowledge, as envisioned by al Faruqi, is acritical, revivalistic response to intellectual modernity.' Its objective is atimeless but it can only be realized by challenging it and engagingMuslim scholars in debate over it. By so doing, we are able to refine thework plan for Islamization. The following critique is therefore presentedin the hope that its suggestions will contribute toward an authenticIslamic tespotlse to intellectual modernity.Exposition of IslamizationFor al Faruqi (1982), the some of the crisis of Muslim society liesin the mdem-Islamic dichotomy of the current educational system. Thecolonial, and therefore alien, vision still survives and is being disseminatedthrough educational institutions, which are the breeding ground ofself-estrangement from Islam. Such early educational reformem as SayyidAhmad Khan and Muhammad 'Abduh did not realize the harm of modemknowledge, for they assumed thatmodem subjects are harmless and can only lend sttength to theMuslims. Little did they realize that the alien humanities, socialsciences, and indeed the natural sciences as well, wee facets ofan integral view of reality, of life and the world, of history, thatis equally alien to that of Islam. (Ibid.)One of his particular concerns is the harmful influence of a universityeducation on a Muslim student whose sentimental attachment to Islamcannot withstand the onslaught of scientific truth. After four years ofalienating influence, his/her Islamic consciousness would be ravaged. Thesolution to this alienation is to be found in the Islamization of knowledge,an understanding that seeks to rebuild the humanities, as well as the socialand natural sciences, in order to establish them fitmly on an Islamic basisconsistent with Islamic objectives. Every discipline is to be "recast" toembody the principles of Islam and remolded to incorporate the"relevance" of Islam along a triple axis constitutive of tawhid (unity) ...